A Nineteenth Century Literary Representation of Nova Scotia Dialect - Falk, Lilian (Papers from the Annual Meetings of the Atlantic Provinces Linguistic Association (PAMAPLA) / ACTES DES COLLOQUES ANNUELS DE L’ASSOCIATION DE LINGUISTIQUE DES PROVINCES ATLANTIQUES (ACAALPA)., 1994)
In 1895 British novelist and playwright Israel Zangwill (1864-1926) published his third novel The Master. The book, which chronicles the career of a Nova Scotian who becomes a successful painter in London, was believed to be based on the life of Halifax-born painter Gilbert Stuart Newton (1794-1835). In describing the hero’s early life in Nova Scotia, Zangwill used many dialect forms as well as words and expressions which are now recognized as Canadianisms. Using biographical and lexicographic data the paper tries to discover the sources Zangwill may have used to create the dialect representation in his book. The paper proposes that it was Zangwill’s friend, the artist George Hutchinson, rather than Newton, who served as model for the book’s hero and was the likely informant regarding Nova Scotia speech.